2013
DOI: 10.2516/ogst/2012010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Natural Gas Compositions on CNG Fast Filling Process for Buffer Storage System

Abstract: Résumé -Effets des compositions de gaz naturel sur le processus de remplissage rapide de GNC pour un système de stockage tampon -La modélisation précise du processus de remplissage rapide des bouteilles de Gaz Naturel Comprimé (GNC) pour l'alimentation de véhicules constitue un processus complexe et doit être parfaitement étudiée. Les conditions finales dans la bouteille doivent satisfaire à des normes de sécurité. La composition du gaz naturel joue un rôle important sur les propriétés thermodynamiques et en c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 15 publications
9
21
0
Order By: Relevance
“…Other thermodynamic properties are then obtained from thermodynamic tables. Farzaneh-Gord et al (2007, 2008a, 2008b, 2012a, 2012b, 2013a have used the same method to analyse the filling process of an adiabatic cylinder. Here, the energy equation for the cylinder wall was also solved simultaneously to determine the inside wall temperature.…”
Section:  mentioning
confidence: 99%
See 2 more Smart Citations
“…Other thermodynamic properties are then obtained from thermodynamic tables. Farzaneh-Gord et al (2007, 2008a, 2008b, 2012a, 2012b, 2013a have used the same method to analyse the filling process of an adiabatic cylinder. Here, the energy equation for the cylinder wall was also solved simultaneously to determine the inside wall temperature.…”
Section:  mentioning
confidence: 99%
“…It was also found that ambient temperature influences the filling process and storage capacity (Shipley, 2002). Farzaneh-Gord et al (2007, 2008a, 2008b, 2012b, 2012c, 2013b have also simulated the fast filling process of CNG in several studies. The results indicated that ambient temperature has considerable effects on the filling process and final cylinder conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heat lost from the on-board NGV cylinder to environment could be calculated as (11) Combining 5, 10 and 11, one could calculate the above equation as: (12) Or in the following form: (13) The above equation could be rearranged in the following form:…”
Section: First Law Analysismentioning
confidence: 99%
“…5 shows scattered error according to Eq. 6 for these compositions, And also Fig 6. for Turkman gas [14] show relative error between AGA8 EOS and ANN results and it can be understood from all scattered figures that errors for this trained ANN are less than 0.5% that it guarantees the good training ANN. IV.…”
Section: Resultsmentioning
confidence: 99%